The Impact of AI-Informed Leadership on Supply Chain Resilience under Global Disruptions: The Mediating Role of Operational Digitalization and the Moderating Role of Human Capital Efficiency (International Journal of Financial, Administrative and Economic Sciences, 2026)
This study aims to analyze the impact of AI-informed leadership on supply chain resilience in Iraqi industrial and service firms under global disruptions, while examining the mediating role of operational digitalization and the moderating role of human capital efficiency. The study is based on a central problem related to the need for organizations to strengthen their leadership, operational, and human capabilities in order to respond effectively to turbulent environments. The research adopted a descriptive-analytical approach, and data were collected through a questionnaire distributed to a sample of 361 respondents drawn from managers and employees working in management, operations, supply chain, and technology-related functions. The findings revealed high levels of AI-informed leadership, operational digitalization, supply chain resilience, and human capital efficiency. The results of structural equation modeling and regression analysis also showed that AI-informed leadership has a positive and significant effect on supply chain resilience. Operational digitalization was found to play a partial mediating role in this relationship, while human capital efficiency strengthened this effect through its moderating role. The study concludes that building a resilient supply chain does not depend on technology alone, but rather requires integration between smart leadership, operational digitalization, and human capabilities. This provides a practical basis for improving organizational performance and enhancing preparedness in the face of disruptions.
Keywords: AI-Informed Leadership; Supply Chain Resilience; Operational Digitalization; Human Capital Efficiency; Global Disruptions